The Prevalence, Usage Patterns, and Complications of Contact Lens Use Among University Students in Damascus, Syria: A Cross‐Sectional Cohort Study - Fares Kahal; Sedra Al‐Habal; Saeed Kadri; Omar Helwani; André Torbey (Health Science Reports, 2025)
ABSTRACT Background Contact lenses are widely used globally, primarily for vision correction and cosmetic enhancement. However, improper handling can lead to many complications. Understanding wearer practices and risk factors is crucial to prevent these adverse effects. This study aims to assess the prevalence of contact lens (CL) wearers among Syrian Private University students, their cleaning and care practices, and potential risk factors linked to complications and symptoms. Methods and Materials This cross‐sectional study was conducted at the Syrian Private University (SPU) from December 2022 to April 2023. Data was collected from 500 students who met the inclusion and exclusion criteria. Data on demographics, hygiene practices, and complications were collected via a paper‐based questionnaire. Statistical analysis was performed using SPSS 25.0, with significance set at p < 0.05. Results Participants were predominantly females (88.8%) with a mean age of 22.41 years. Most participants used contact lenses without a valid prescription (64.6%) for aesthetic reasons (44.3%). The main vision problems were myopia (38.9%), astigmatism (10.3%), and hyperopia (4%). Complications included red eye (68%), dacryorrhea (63%), dry eye (58.4%), and blurred vision (43%). Factors significantly associated with various ocular complications include showering or swimming while wearing contact lenses, sharing lenses, exceeding the recommended renewal period, and improper or inconsistent use of contact lens solutions. Conclusion Our findings indicate that improper contact lens use and non‐prescribed acquisitions are prevalent among Syrian university students, driven largely by cosmetic motives. These behaviors contribute to preventable ocular complications, underscoring a critical public health concern. The results highlight the need for regulatory measures, targeted education, and clinical interventions to promote safe practices, reduce complications, and safeguard eye health within the population.